The health curriculum in Philippine basic education : a resource book on health for teachers, volume 2 - Galvez Tan, Jaime Z.; Vicencio, Evelina M.;Baquiran, Raymundo S.;Dionisio, Allan R. ;Parawan, Amado R.;Reyes-Sumayo, Grace;See, Carmelea Ang (Pasay City, Philippines : UNESCO, National Commission of the Philippines, 2009)
The book is divided into the 10 health areas prescribed by the World Health Organization.
Chapter 1 : Growth and development -- Chapter 2 : Nutrition -- Chapter 3 : Personal health -- Chapter 4 : Mental health -- Chapter 5 : Health promotion and prevention of diseases -- Chapter 6 : Substance use and abuse -- Chapter 7 : Safety and first aid -- Chapter 8 : Family life -- Chapter 9 : Consumer health -- Chapter 10 : Community health -- Chapter 11 : Environmental health
Includes bibliographical references.
Keywords: HEALTH EDUCATION -- CURRICULA -- PHILIPPINES